Model Model Pembelajaran Kooperatif - Dony Agus Prasetyo; Muhammad Badruddin Zarkasyi; Sarwanto Sarwanto; Taufiqurahman Taufiqurahman (Lembaga Yasin AlSys, 2026)
Although cooperative learning has been widely used as a cooperation-based learning model, conceptual understanding of its characteristics, objectives, elements, principles, procedures, and application techniques still needs to be examined systematically. This article aims to examine the concept of cooperative learning as a model that positions students as active subjects in the learning process through group cooperation to achieve shared learning objectives. This study used a library research method by analyzing various relevant literature on cooperative learning. The results of the review indicate that cooperative learning can improve academic learning outcomes, social skills, communication skills, individual responsibility, and attitudes of mutual respect for differences among students. The success of this model is supported by positive interdependence, individual responsibility, face-to-face interaction, effective communication, and group evaluation. Various techniques that can be applied include Student Teams Achievement Division (STAD), Group Investigation, Jigsaw, Teams Games Tournament (TGT), Structural Type, and Two Stay-Two Stray. Thus, cooperative learning can serve as an effective alternative learning strategy to create an active, collaborative, communicative, and meaningful learning atmosphere.